Antibacterial and Antibiofilm Activities of the Photothermal Therapy Using Gold Nanorods against Seven Different Bacterial Strains - Castillo Martínez, Juan Carlos; Martínez Castañón, Gabriel Alejandro; Martínez Gutiérrez, Fidel; Zavala Alonso, Norma Verónica; Patiño Marín, Nuria; Niño Martínez, Nereyda; Zaragoza Magaña, Valentín; Cabral Romero, Claudio (2015)
The objective of this work was to determine the bactericidal and antibiofilm activities of gold nanorods (AuNRs) using plasmonic photothermal therapy (PPTT) against oral microorganisms. AuNRs were synthesized by the seed and growth solution method and the gold nanoclusters were characterized with a size of 33.2 nm ± 2.23 length and 7.33 nm ± 1.60 width. The efficacy of PPTT related to its temperature was done reaching 67∘ C. Minimum inhibitory concentration (MIC) and minimum bactericide concentration (MBC) of AuNRs and AuNRs PPTT were determined against Enterococcus faecalis, Staphylococcus aureus, Streptococcus mutans, Streptococcus sobrinus, Streptococcus oralis, Streptococcus salivarius, and Escherichia coli growth. The antibiofilm activity of AuNRs was explored by fluorescence microscopy. After experimental analyses, AuNRs PPTT shows better results in MICs and MBCs, when it was compared with AuNRs alone. The laser employed to activate the AuNRs had no antibacterial effect against oral microbes. The MICs and MBCs values were higher for S. aureus and E. coli and lower against S. oralis. Surprisingly, the AuNRs alone presented a high antibiofilm activity, inhibiting the biofilm formation of S. mutans. Altogether, these results strongly suggest that AuNRs could be an interesting option to control oral biofilms.